LIFE INSURANCE CLAIMS DISPUTE RESOLUTION THROUGH THE CONSUMER DISPUTE RESOLUTION AGENCY (BPSK) - Adi Salamat, Padian; Mansar, Adi; Arifin, Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Life insurance claim dispute resolution is a crucial aspect of consumer legal protection in Indonesia, particularly when claims are rejected by insurance companies. The Consumer Dispute Resolution Agency (BPSK) was established as an alternative out-of-court dispute resolution body, aiming to provide fast, simple, and low-cost resolution. However, in practice, the effectiveness of the BPSK in resolving life insurance claim disputes still faces various obstacles. This study aims to determine the procedures for resolving life insurance claim disputes through the BPSK, identify the obstacles encountered, and analyze efforts to optimize the resolution of these disputes. This study uses a normative legal research method with a statutory and conceptual approach, supported by primary, secondary, and tertiary legal materials. Data collection was conducted through literature review and qualitative analysis. The results indicate that life insurance claim dispute resolution through the BPSK is carried out through mediation, conciliation, and arbitration mechanisms, with final and binding decisions. However, its effectiveness still faces obstacles, including overlapping authority with the Financial Services Authority (OJK), weak enforcement powers of decisions, the technical complexity of insurance disputes, an imbalance in the bargaining position between consumers and businesses, and limited institutional capacity of the BPSK. Optimization efforts that can be implemented include strengthening regulations, harmonizing authority between institutions, increasing human resource capacity, increasing business compliance, and improving public legal and financial literacy. Therefore, strengthening the role of the BPSK is essential to realizing effective legal protection for consumers in life insurance claim disputes in Indonesia